Analisis Pelaksanaan Pengawasan Upah Minimum Sektor Perkebunan Kelapa Sawit Di Provinsi Sumatera Selatan - Putra, Desvi Triansyah; Lisdiana, Lisdiana; Berlian, Ong (@-Publik: Jurnal Administrasi Publik, 2025)
The Supervision of Sectoral Minimum Wage in South Sumatra Province is an activity aimed at ensuring that every employer and company in South Sumatra Province, in providing wages to workers, does not deviate from the Sectoral Minimum Wage set by the Governor of South Sumatra Province. In practice, there are often deviations from the Minimum Wage for Workers in palm oil plantation companies. One of the issues is the lack of supervision over wages that do not comply with the provisions of the South Sumatra Provincial Sectoral Minimum Wage, which has been established. Some companies fail to pay overtime according to the Sectoral Minimum Wage for workers who work more than 8 hours a day. There is also a lack of strict penalties for companies that do not comply with the legal provisions on Minimum Sectoral Wage determination, and a lack of awareness among companies about the importance of the South Sumatra Provincial Sectoral Minimum Wage. Furthermore, there is insufficient information and socialization provided by the South Sumatra Provincial Manpower Office to companies regarding the minimum wage system for labor and the standards set by companies for their employees. The purpose of this research is to analyze the Implementation of Supervision of the Sectoral Minimum Wage for Palm Oil Plantation in South Sumatra Province. The results revealed that some aspects have been implemented effectively, while others have not, such as setting the measurement and standards, which oblige companies to establish the Sectoral Minimum Wage for Palm Oil Plantation in South Sumatra Province, amounting to 3,404,177 as of February 3, 2022, following the provisions of Law No. 11 of 2021.